Electronic structure and magnetic properties of N monodoping and (Ag, N) codoped graphene-like ZnO sheet. (November 2014) - Zhang, W. X.; Bai, Y. X.; He, C.; Xu, L.; Li, H.; Duan, L.; Wu, X. L.; Hu, X.
Abstract : We perform first principles density functional theory calculations to investigate the atomic structures, electronic structures and magnetic properties of dopant complexes involving Ag and N in graphene-like ZnO sheet (Gr–ZnO). The results indicate that monodoping of N in Gr–ZnO favours a spin polarised state. Ag substituted on the cation site (AgZn ) acts as a single acceptor and exhibits a strong attractive interaction with a nitrogen acceptor located at the nearest neighbour oxygen site, forming passive Ag–N complex. By introducing a higher concentration of nitrogen, Ag–2N complex forms. The ferromagnetism is decreased, but the formation energy can be evidently reduced for the defective system. Our findings suggest that (Ag, N) codoping of Gr–ZnO could turn the ferromagnetic stability and is likely to yield better p -type conductivity.